2003
DOI: 10.3136/fstr.9.30
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aspartic Proteinase from Basidiomycete, Laetiporus sulphureus

Abstract: Aspartic proteinase from Laetiporus sulphureus was purified by sequential chromatographies on Sephadex G-100, DEAE-Sepharose Fast Flow, and Butyl-Toyopearl 650S. The final preparation was judged homogeneous by SDS-PAGE. The molecular mass of the purified enzyme was estimated to be 50,000 and the isoelectric point of the enzyme was 3.5. The enzyme was most active at pH 2.6 and was inhibited completely by a specific aspartic proteinase inhibitor, pepstatin A. The enzyme was extremely labile as compared to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The enzyme called polyporopepsin (EC 3.4.23.29) was cloned and sequenced (Kobayashi et al 1989). Its N-terminal amino acid sequence bears close resemblance to that of aspartic proteinase from the basidiomycete Laetiporus sulphureus (Kobayashi and Kim 2003).…”
Section: Hydrolasesmentioning
confidence: 99%
“…The enzyme called polyporopepsin (EC 3.4.23.29) was cloned and sequenced (Kobayashi et al 1989). Its N-terminal amino acid sequence bears close resemblance to that of aspartic proteinase from the basidiomycete Laetiporus sulphureus (Kobayashi and Kim 2003).…”
Section: Hydrolasesmentioning
confidence: 99%
“…Isolation, Purification, and Properties of EPS-2-1 According to the phenol-sulfuric acid method, the EPS purified from L. sulphureus contained 98.9% of carbohydrates and no absorbance was observed under the UV 280nm spectrophotometer, indicating that it was not contaminated with other substances including proteins [16]. The EPS was purified by a DEAE cellulose column with gradient elution using 0-0.3 M NaCl solutions.…”
Section: Resultsmentioning
confidence: 99%
“…No absorbance was estimated at 280 nm in the UV spectrophotometer. This indicated that the exopolysaccharide was not contaminated with other substances, including proteins (Kobayashi and Kim, 2003). A linkage analysis was performed with full methylation, reduction, and acetylation of purified polysaccharide.…”
Section: Exopolysaccharide Productivity (G/l)mentioning
confidence: 99%